Prosecutorial Power: Ending Prosecutions Through Restorative Justice Principles: Kekuasaan Penuntutan: Mengakhiri Penuntutan Melalui Prinsip-Prinsip Keadilan Restoratif - Faisol, Faisol; Anadi, Yandri Radhi (Universitas Muhammadiyah Sidoarjo, 2024)
This data article delves into the evolving landscape of criminal law enforcement through the lens of prosecutors' authority to terminate prosecutions using restorative justice principles. Utilizing a normative research approach, it scrutinizes Attorney General Regulation Number 15 of 2020 on Termination of Prosecution Based on Restorative Justice alongside statutory regulations Number 11 of 2021 and the concept of restorative justice itself. The study reveals that prosecutors indeed possess the power to end prosecutions when cases are resolved outside the courtroom, as evidenced by the issuance of the Decree on Termination of Prosecution (SKPP). This approach, rooted in article 35 paragraph (1) letters c and J of the Republic of Indonesia Prosecutor's Law, signifies a delegation of authority from the Attorney General to the Public Prosecutor. These findings emphasize the compatibility of restorative justice practices with the fundamental objectives of criminal law enforcement. Highlights: Prosecutor's Authority: Prosecutors have the authority to discontinue prosecution based on restorative justice principles. Out-of-Court Settlement: SKPP is issued after out-of-court settlement of criminal cases through restorative justice mechanisms. Legal Basis: The legal basis for such action is the Indonesian Prosecutor Law Article 35 paragraph (1) letter c and J, which confirms the delegation of authority from the Attorney General to the Public Prosecutor. Keywords: Termination of Prosecution, Criminal, Restorative Justice